A Phenomenological Study on Moral Education of the Minahasa Children in Manado - Rahmatullah, Azam Syukur; Suud, Fitriah M.; Putro, ‪Khamim Zarkasih (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
A family is the first place that impacts various elements of children's growth and development, especially their social growth. Procedures and conditions in the family are suitable environments for social children. Purposing to analyze the role of Muslim parents of the Minahasa Tribe in Tomohon, Manado, Indonesia, in educating children's morals in Islamic minority communities with a local cultural approach, this research uses phenomenological study methods with a qualitative approach. Researchers found that local culture-based moral education in the formation of children's character/morals in Tomohon became one of the concerns of more than the government and even the community and parents to be able to maintain and preserve a valuable character education process from ancient times so that the current generation can understand the value of manners, mutual respect, respect for parents is critical to forming attitudes and moral. Moral education based on local cultural values in the formation of children's character/morals in Tomohon has a very drastic value from parents past and present to educate their children. It makes children open to each other; they consider their parents as friends when discussing problems in the family.